2004
DOI: 10.1063/1.1786678
|View full text |Cite
|
Sign up to set email alerts
|

A physically based model for the spatial and temporal evolution of self-interstitial agglomerates in ion-implanted silicon

Abstract: A physically motivated model that accounts for the spatial and temporal evolution of self-interstitial agglomerates in ion-implanted Si is presented. For the calibration of the model, a genetic algorithm is used to find the optimum set of physical parameters from experimental data. Mean-size evolution of {113} defects obtained by transmission electron microscopy and self-interstitial oversaturation results measured in the vicinity of extended defects are combined in the same fitting procedure. The calibration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 42 publications
1
39
1
Order By: Relevance
“…Still, it is worth discussing briefly a particular extended defect known as the {311} defect. {311} defects have been studied in much detail [15,[62][63][64][65]. They are rod-shaped accumulations of Si i s in {311} planes of the Si lattice (see Fig.…”
Section: {311} Defectsmentioning
confidence: 99%
“…Still, it is worth discussing briefly a particular extended defect known as the {311} defect. {311} defects have been studied in much detail [15,[62][63][64][65]. They are rod-shaped accumulations of Si i s in {311} planes of the Si lattice (see Fig.…”
Section: {311} Defectsmentioning
confidence: 99%
“…Within this approach based on the mean-field approximation, the diffusion and nucleation/growth of defects is modelled through a set of diffusion-reaction rate equations. Different research teams [11,14,18,23,26] have used this approach to study the nucleation and growth of defects in various materials over the years. Recently, Rottler et al [20] used the RT formalism to investigate point defect dynamics in metals and showed that, when defects are homogeneously distributed, kMC and RT models are in near perfect agreement.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the same two types of dislocation loops were found in silicon after ''irradiation", actually ion implantation, and it took us a while and lots of experiments to understand then model the formation and thermal evolution of these defects. Today, it is understood and physically based models exist, either analytical or based on Monte Carlo methods, which have been implemented in academic and commercial codes aimed at predicting the effect of processes in semiconductors [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%